Identification and Characterization of Bacillus cereus SW7-1 in Bombyx mori (Lepidoptera: Bombycidae). Issue 1 (25th September 2015) - Li, Guan-Nan; Xia, Xue-Juan; Zhao, Huan-Huan; Sendegeya, Parfait; Zhu, Yong
Abstract : The bacterial diseases of silkworms cause significant reductions in sericulture and result in huge economic loss. This study aimed to identify and characterize a pathogen from diseased silkworm. SW7-1, a pathogenic bacterial strain, was isolated from the diseased silkworm. The strain was identified on the basis of its bacteriological properties and 16S rRNA gene sequence. The colony was round, slightly convex, opaque, dry, and milky on a nutrient agar medium, the colony also exhibited jagged edges. SW7-1 was Gram-positive, without parasporal crystal, and 0.8–1.2 by 2.6–3.4 µm in length, resembling long rods with rounded ends. The strain was positive to most of the physiological biochemical tests used in this study. The strain could utilize glucose, sucrose, and maltose. The results of its 16S rRNA gene sequence analysis revealed that SW7-1 shared the highest sequence identity (>99%) with Bacillus cereus strain 14. The bacterial strain was highly susceptible to gentamycin, streptomycin, erythromycin, norfloxacin, and ofloxacin and moderately susceptible to tetracycline and rifampicin. It exhibited resistance to other antibiotics. SW7-1 had hemolytic activity and could produce extracellular casease, lipase, and amylase. SW7-1 could reproduce septicemia-like symptoms with high mortality rate when re-fed to healthy silkworm. .The median lethal concentration (LC50 ) was 5.45 × 10 4 cfu/ml. Thus, SW7-1 was identified as B. cereus, which is a pathogen for silkworm and human infections are possible.